Rethinking Language Proficiency: Commentary on Hulstijn (2024) - Lourdes Ortega; Shu-Ling Wu (Languages)
We enjoyed reading Jan Hustijn’s update of his Basic Language Cognition (BLC) theory in the pages of Languages (Hulstijn, 2024), and we are honored to provide a commentary here. Researchers, language learners, and educators hold varying definitions and understandings of language proficiency. Innovative work that helps researchers in the field rethink proficiency is therefore of utmost importance. Hulstijn’s BLC theory offers a clear, well-motivated, and comprehensive framework for investigating what language proficiency may be, what ceilings there may be in what can be attained, and what causes there may be for attainment differences. Hulstijn tells us that BLC rests on a metatheory (i.e., a foundation of assumptions) of language and language learning grounded in two areas familiar to most scholars in second language acquisition (SLA): usage-based linguistics and complex systems. He offers BLC as a theory, that is, a tool to empirically investigate the causation and development of a phenomenon, in this case, proficiency, through a well-articulated research program. In this commentary, we highlight some aspects of the updated BLC theory that we find most useful. Following the Popperian spirit embraced by Hulstijn, we also introduce some critical probes subjects for refinements that may benefit BLC theory in the future.